Analytical Network Process (ANP) Model For Maqashid Sharia-Based Halal Tourism Development - Mukti, Titania; Andriyanto, Gian Anggraeni (Indonesia, 2024)
Kapota Island is part of the Wakatobi region, Southeast Sulawesi, which is one of the ten best tourist destinations in Indonesia and has been recognized by the United Nations Educational, Scientific and Cultural Organization (UNESCO) as a biosphere reserve that has underwater natural beauty. Tourism potential on Kapota Island includes Lake Taelaron Nto'o Oge, Cave of the Gods, Kolofofa Beach, Togo Molengo Fort, and Manohara Bridge. The population of Kapota Island is entirely Muslim, but there is an imbalance in terms of halal tourism development due to the lack of optimal tourism management by the local community and the absence of assistance from the Regional Government. This study aims to analyze the problems in the halal tourism development policy on Kapota Island from the maqasyid sharia perspective. The research method uses soft system methodology with analytical network process model. The type of data used is primary data directly obtained from the first source. Data collection techniques were carried out by interviews, themed discussions with the village head and the community, and documentation. Then the research data is described in depth. Data analysis used analytical network process (ANP). The results showed that the development of halal tourism on Kapota Island has not been optimal in implementing the five core points of maqasyid sharia and certification standards of cleanliness, health, safety, environmental sustainability of the Regulation of the Minister of Tourism and Creative Economy of the Republic of Indonesia Number 13 of 2020. The Kapota Island halal tourism development model needs to be designed to overcome the problems of transportation access, living and worship facilities, as well as the development of local community resources in managing halal tourist destination areas.